Evaluating the Effect of Resection on the Sealing Ability of MTA and CEM Cement - Salem Milani, Amin; Shakouie, Sahar; Borna, Zahra; Sighari Deljavan, Alireza; Asghari Jafarabadi, Mohammad; Pournaghi Azar, Fatemeh (Iranian Endodontic Journal, 2012)
Introduction: In cases of limited access to the surgical site, an alternative approach is to obturate the canal prior to surgery. Endodontic surgery is subsequently performed by root-end resection without retro-cavity preparation. This in vitro study was designed to compare the sealing ability of resected roots filled with either mineral trioxide aggregate (MTA) or calcium enriched mixture (CEM) cement. Materials and Methods: Seventy maxillary anterior teeth were selected. Following canal preparation, the teeth were randomly divided into four experimental (n=15) and two control (n=5) groups. In Group 1, CEM cement was placed into the apical 6-mm of the canal. The remainder of the canal was filled with gutta-percha/AH26 and 3-mm root-ends were resected. In Group 2: the teeth were treated as described above except that MTA was used instead of CEM cement. Group 3: The canals were obturated with gutta-percha/AH26. After root-end resection, retro cavities were prepared and filled with CEM cement. Group 4: The teeth were treated as described for group 3 except that MTA was used instead of CEM cement. The root apices of teeth were then placed in India ink, and maximum dye penetration was measured with a stereomicroscope. Nested ANOVA and Independent samples t-test were used to evaluate the statistical significance. Results: The mean dye leakage values for groups 1 to 4 were 402.6, 526.4, 141.0, and 177.4, respectively. The retrofilled groups had less microleakage compared to the resected materials; in the CEM cement groups this was statistically significant (P<0.05), i.e. root-end resection had no significant influence on the sealing ability of MTA, but significantly increased the microleakage of CEM cement (P=0.017). Overall, CEM cement showed less microleakage compared to MTA, however the difference was not significant. Conclusion: Within the limitations of this dye leakage study, we can conclude that if limited access prohibits retrofill placement, MTA or CEM cement can be used to fill the canal prior to root-end resection; as they have similar sealing ability. However, further laboratory and clinical studies are required to evaluate this alternative method.